Digital Transformation and the Legality of MSMEs: Implementation of NIB, Logo, and Business Banner in Sangon II Hamlet - Anggun Nur Aini; Chilya Aghnis Shalicha; Muhammad Wildan Khilmi; Alif Ahsan Ibnu Fathoni; Muhammad Misbahul Munir; Checar Dwi Arsi; Imas Ayu Wardani; Danang Jati Setiawan; Fadhilah Hafizh Nugroho; Ridho Rizqulloh (UIN Sunan Kalijaga, 2026)
Abstract - Digital transformation has become a fundamental need for the development of Micro, Small and Medium Enterprises (MSMEs) in facing competition in the modern era. Business legality through the issuance of a Business Identification Number (NIB) is an important first step to provide legal certainty, access to capital, and market development opportunities. This article discusses the implementation of digital transformation and legality of MSMEs in Sangon II Hamlet with a focus on the issuance of NIB, logo making, and banner installation as a business visual identity. The method used is descriptive qualitative through direct observation and assistance to local MSME actors. The results of the activity show that business legality with NIB not only increases consumer and business partner confidence, but also opens access to government programs. Meanwhile, the use of logos and banners can strengthen business image, increase marketing appeal, and become the first step towards digital branding. Thus, digital transformation accompanied by business legality can be an effective strategy in strengthening the competitiveness of local MSMEs. Keyword: Digital transformation, MSME legality, NIB, logo, banner, Sangon II Hamlet. Abstrak - Transformasi digital telah menjadi kebutuhan mendasar bagi perkembangan Usaha Mikro, Kecil, dan Menengah (UMKM) dalam menghadapi persaingan di era modern. Legalitas usaha melalui penerbitan Nomor Identitas Bisnis (NIB) merupakan langkah awal yang penting untuk memberikan kepastian hukum, akses terhadap modal, serta peluang pengembangan pasar. Artikel ini membahas implementasi transformasi digital dan legalitas UMKM di Dusun Sangon II dengan fokus pada penerbitan NIB, pembuatan logo, dan pemasangan spanduk sebagai identitas visual usaha. Metode yang digunakan adalah kualitatif deskriptif melalui observasi langsung dan pendampingan kepada pelaku UMKM setempat. Hasil kegiatan menunjukkan bahwa legalitas usaha dengan NIB tidak hanya meningkatkan kepercayaan konsumen dan mitra bisnis, tetapi juga membuka akses ke program-program pemerintah. Sementara itu, penggunaan logo dan spanduk dapat memperkuat citra usaha, meningkatkan daya tarik pemasaran, dan menjadi langkah awal menuju branding digital. Dengan demikian, transformasi digital yang disertai dengan legalitas usaha dapat menjadi strategi yang efektif dalam memperkuat daya saing UMKM lokal. Kata kunci: Transformasi digital, legalitas UMKM, NIB, logo, spanduk, Dusun Sangon II.